Potential predation of a mud turtle by a jaguar (Panthera onca): evidence from camera traps in the Mexican Maya Forest - Rodríguez-Luna, César R.; Diaz-Gamboa, Luis; Ibarra-Cerdeña, Carlos N. (Therya Notes, 2025)
The jaguar (Panthera onca), a large felid widely distributed across the Americas, exhibits an opportunistic diet primarily composed of mammals, birds, and reptiles. While reptile consumption is well-documented in the southern regions of its range, such behavior is rarely observed in Mexico, particularly with chelonians. This study presents photographic evidence of a potential predation event involving a jaguar and a mud turtle (Kinosternon sp.) in the Mexican Maya Forest. Between November 2022 and February 2024, we conducted camera trap surveys to monitor wild vertebrates inhabiting the Maya Forest within the Calakmul Biosphere Reserve, Campeche, Mexico. At the conclusion of the monitoring period, we retrieved the digital data recorded by the devices to identify the documented species. Through 4,705 trap-nights of sampling effort, we obtained photographic evidence of the vertebrate community inhabiting the region. In November 2023, we recorded an image of a subadult jaguar holding a mud turtle (Testudines: Kinosternidae) in its jaws. The species of the turtle was unidentified but is presumed to belong to the genus Kinosternon. These findings enhance our understanding of the jaguar's dietary flexibility in tropical forest ecosystems and highlight the value of camera traps as effective tools for studying ecological interactions in predator-prey systems.